1985
DOI: 10.1056/nejm198503073121004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blood Glucose Control on Increased Glomerular Filtration Rate and Kidney Size in Insulin-Dependent Diabetes

Abstract: To investigate the relation between blood glucose control on the one hand and an increased glomerular filtration rate and enlarged kidneys on the other, we studied 12 patients with insulin-dependent diabetes and an increased glomerular filtration rate for a year after they were randomly assigned either to continuous subcutaneous insulin infusion or to unchanged conventional therapy. Glycemic control, measured by mean plasma concentrations of glucose and glycosylated hemoglobin, was rapidly and significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
1
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(116 citation statements)
references
References 21 publications
9
105
1
1
Order By: Relevance
“…Mean GFR decreased from 150 to under 130 ml min −1 1.73 m −2 and was maintained at this level over 12 months, whereas GFR was unchanged in the control group. At 1 month after cessation of insulin pump therapy, GFR rebounded into the hyperfiltration range [1]. This indicates that glycaemic control remains an active modulator of GFR several years after onset of diabetes.…”
Section: Effect Of Glycaemic Control On Hyperfiltration In Type 1 Diamentioning
confidence: 89%
See 2 more Smart Citations
“…Mean GFR decreased from 150 to under 130 ml min −1 1.73 m −2 and was maintained at this level over 12 months, whereas GFR was unchanged in the control group. At 1 month after cessation of insulin pump therapy, GFR rebounded into the hyperfiltration range [1]. This indicates that glycaemic control remains an active modulator of GFR several years after onset of diabetes.…”
Section: Effect Of Glycaemic Control On Hyperfiltration In Type 1 Diamentioning
confidence: 89%
“…There is clear evidence that prolonged intensive insulin therapy, even after 12 years of diabetes, can normalise hyperfiltration [1]. In a prospective study of 12 patients with type 1 diabetes, hyperfiltration and mean HbA 1 over 10%, six were randomised to insulin pump therapy and six to conventional therapy for 12 months.…”
Section: Effect Of Glycaemic Control On Hyperfiltration In Type 1 Diamentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic patients, the size of the kidney is increased during insulin treatment and in most studies it remains 20-30 % larger [12,13,14]. Complete normalization of kidney size is not achieved in patients even after intensive treatment [14][15][16][17]. In experimental diabetes, preserving kidney weight by insulin treatment from the beginning of the disease is possible [18] but if treatment is started later the kidney weight cannot be completely normalized [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mogensen et al (1983) found that during the first three stages of diabetic nephropathy (up to 10-15 years after diagnosis), glomerular filtration rate (GFR) is increased by 20-40%, which may be related to increased kidney size (Mogensen & Anderson, 1973), and may be normalised by strict glycaemic control (Wiseman et al, 1985). All of our patients had normal or near normal plasma creatinine values (see Table 1) and did not suffer from polyuria.…”
Section: Discussionmentioning
confidence: 53%